Розвиток творчих здібностей молодших школярів: психолого-педагогічний контекст - Лук’янчук, Мар’яна; Lukyanchuk, Mariana (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто різні підходи науковців до трактування поняття «творчі здібності», їх змісту та структури. Як наслідок, розмежовано два суміжних, проте не тотожних поняття «творчі» та «креативні» здібності. А також проаналізовано психолого-педагогічні засади розвитку творчих здібностей у молодших школярів. Виділено внутрішні і зовнішні фактори впливу на особистість та розвиток загальних і творчих здібностей. The article examines the different approaches to scientific interpretations of "creativity", its content and structure. As a result, delineated two related, but not identical concepts of "creative" abilities and "creativity". Given the generalization of scientific positions on the concept of creative skills, rethinking them in the light of the process of education of primary school children was given a generalized definition: creativity - synthesis features and personality traits that characterize the level of compliance with certain type of creative activity and determine their level of effectiveness. Also in the article analyzed the psycho-pedagogical principles of creative abilities of primary school children and allocated the internal and external factors of influence on personality and on development of common and creative skills. External factors included organized training under the guidance of a teacher. To the internal factors included physiological and social heritage, intellectual, child emotional experience and creative potential. The influence of interaction between teachers and pupils based on personality-oriented nature, was defined as the basis to stimulate the development of creative abilities. It is noted that the development of creative abilities in education of primary school children is characterized by substantial and practical saturation, personal and social value and emotional appeal. The attention focused on minimizing the impact of reproductive methods of education for independent activity of children in the creative activity. In the article was characterized the basic tools and techniques of creative skills development. They are: technique of associative symbols, the concept of creative potential and a game as the most common means of creating interest in children of primary school and "optimistic, humane atmosphere", which includes elements such as competition, leadership, unpredictable situations and zeal. To solve this problem, advisable would be set appropriate consideration and combination of various aspects of creative skills and personal development as a whole.
Development of creative abilities younger pupils: psychological and educational context
Keywords: творча особистість; творчі здібності; креативність; creative personality; creative skills; creativity